Here is one method of obtaining an expression equivalent to the one you derive by hand. We start by defining two functions, $f$ and $g$, which we consider to be functions of $(x,z)$. That is, we consider $\mu$ and $\theta$ to be functions of $(x,z)$. When we take the partial derivatives with regard to $z$ we tell Mathematica that $\mu$ and $\theta$ are functions of $(x,z)$.
f = Cosh[μ] Cos[θ];
g = Sinh[μ] Sin[θ];
df = D[f, z, NonConstants -> {μ, θ}]
dg = D[g, z, NonConstants -> {μ, θ}]
(* -Cosh[μ] D[θ, z, NonConstants -> {θ, μ}] Sin[θ] +
Cos[θ] D[μ, z, NonConstants -> {θ, μ}] Sinh[μ]
Cosh[μ] D[μ, z, NonConstants -> {θ, μ}] Sin[θ] +
Cos[θ] D[θ, z, NonConstants -> {θ, μ}] Sinh[μ] *)
We recognize that $df$ is the change in $z$ with regard to $z$ holding $x$ constant and $dg$ is the change in $x$ with regard to $z$ holding $x$ constant. In other words, we can set $df = 1$ and $dg = 0$ and solve for the derivatives $\partial\mu/\partial z$ and $\partial\theta/\partial z$. We can use Solve[]
for this, but we must make a substitution first. We evaluate
rules =
{D[μ, z, NonConstants -> {θ, μ}] -> dμdz, D[θ, z, NonConstants -> {θ, μ}] -> dθdz};
eqns = {df == 1, dg == 0} /. rules;
soln = Solve[eqns, {dμdz, dθdz}] // First
(* {dμdz -> (Cos[θ] Sinh[μ])/(Cosh[μ]^2 Sin[θ]^2 + Cos[θ]^2 Sinh[μ]^2),
dθdz -> -((Cosh[μ] Sin[θ])/(Cosh[μ]^2 Sin[θ]^2 + Cos[θ]^2 Sinh[μ]^2))} *)
Finally, we want to show that the above expression gives us the same as by a hand calculation:
hand = Cos[θ] Sech[μ]/(Cos[θ]^2 Tanh[μ] + Sin[θ]^2 Coth[μ]);
(dμdz /. soln) == hand // Simplify
(* True *)